Impacts of Urbanization Undermine Nestedness of the Plant–Arbuscular Mycorrhizal Fungal Network - Lin, Litao; Chen, Yun; Xu, Guorui; Zhang, Yuxin; Zhang, Shuang; Ma, Keming (Frontiers in Microbiology, 2021)
● Cities are prone to ecological problems, yet the impacts of rapid global urbanization on the feedback between above- and belowground subsystems remain largely unknown.We sampled the roots of 8 common herbaceous plants within the Fifth Ring (urban areas) and in the Jiufeng National Forest Park (rural areas) in Beijing (China) to assess the impacts of urbanization on the network of plant-arbuscular mycorrhizal (AM) fungal associations. ● Using Illumina MiSeq sequencing, 81 AM fungal OTUs were identified in 78 herb root samples. Urbanization significantly increased the Shannon, Simpson, and Pielou indexes of root AM fungi and the fungal similarity among 8 plants. ● In this study, a significantly nested mycorrhizal association network was observed in rural areas (NODF=64.68), whereas a non-nested pattern was observed in urban areas (NODF=55.50). Competition index C-score (0.0769) of AM fungi in urban areas was slightly lower than that in rural areas (0.1431), and the specificity (d’) of 8 host plants in urban areas was significantly lower than that in rural areas. Convergent adaption may be an important factor influencing the nested pattern of mycorrhizal associations during urbanization. Generalists, rather than specialists, were enhanced during the establishment of mycorrhizal associations in urban areas. ● Our results suggested that reduced selectivity of host plants, and generalist promotion and convergent adaptation of AM fungi during urbanization may contribute to the non-nested network of plant-AM fungal associations.